Impact of warm ambient color on reservation intention: The case of hotel rooms - kawtar oubdi; Mustapha ASBAI; Zineb Ouazzani Touhami (Moroccan Journal of Quantitative and Qualitative Research)
Color is one of the atmospheric dimensions explored within the framework of sensory marketing. Previous studies have primarily examined its effects based on research in psychology. However, it appears that few studies have been conducted specifically in the hotel context, a particularly competitive sector where meeting customer expectations regarding well-being is essential. Moreover, existing studies are generally inspired by the S-O-R model, one of the main limitations of which is the neglect of moderating variables.The objective of this article is to propose a more comprehensive conceptual model, contributing to the enrichment of the existing literature, while emphasizing, on the one hand, its theoretical contribution, and, on the other hand, the crucial importance for practitioners and hotel owners to make an informed and strategic choice regarding the dominant color of the rooms.